The interannual variability of the Indian Ocean subtropical mode water based on the Argo data - Adiwira, Hanani; Suga, Toshio (Frontiers in Marine Science, 2023)
Gaining insight into the interannual variability of the Indian Ocean Subtropical Mode Water (IOSTMW) is essential for understanding ocean dynamics in the Southwest Indian Ocean, since it carries the signal of winter mixing and transports it into the ocean interior. As the number of Argo profiles in the Southwest Indian Ocean increases, it has become possible to study temporal variations in IOSTMW using observation data. We used Argo products to examine the interannual variability of the IOSTMW from 2005 to 2020. We examined various definitions to determine the most suitable definition for IOSTMW in this study, choosing to define the IOSTMW as a layer with a vertical temperature gradient of less than 1°C per 100 meters (dT/dz< 1°C/100 m) and a temperature range of 16°C–18°C because this correlates strongly with winter heat loss in the same year. This method is particularly useful for investigating how mode water captures anomalous winter mixing signals and advects them to the ocean interior via subduction. Furthermore, we found that summer stratification can play a role in either facilitating or hindering the formation of thick IOSTMW layers. Our study indicates that thin IOSTMW layers are primarily caused by extremely weak winter heat loss associated with anomalously weak latent heat, whereas thick IOSTMW formation is aided by weak summer stratification.